Labeling of cancer cells with magnetic nanoparticles for magnetic resonance imaging - Weis, Christian; West, Adrian; Blank, Fabian; Black, Gregory; Woodward, Robert C.; Carroll, Matthew R. J.; Mainka, Astrid; Kartmann, René; Brandl, Anna; Bruns, Heiko; Hallam, Elizabeth; Shaw, Jeremy; et al. (Magnetic Resonance in Medicine, 2014)
The process of invasion and metastasis formation of tumor cells can be studied by following the migration of labeled cells over prolonged time periods. This report investigates the applicability of iron oxide nanoparticles as a magnetic resonance imaging (MRI) contrast agent for cell labeling.?Fe2 O3 nanoparticles prepared with direct flame spray pyrolysis are biofunctionalized with poly-l-lysine (PLL). The nanoparticles within the cells were observed with transmission electron microscopy, bright-field microscopy, and magnetorelaxometry. MRI of labeled cells suspended in agarose was used to estimate the detection limit.PLL-coated particles are readily taken up, stored in intracellular clusters, and gradually degraded by the cells. During cell division, the nanoparticle clusters are divided and split between daughter cells. The MRI detection limit was found to be 25 cells/mm(3) for R2*, and 70 cells/mm(3) for R2. The iron specificity, however, was higher for R2 images. Due to the degradation of intracellular ?Fe2 O3 to paramagnetic iron ions within 13 days, the R1, R2, and R2* contrast gradually decreased over this time period to approximately 50% of its initial value.These results suggest that PLL-coated ?Fe2 O3 nanoparticles can be used as an MRI contrast agent for long-term studies of cell migration. Magn Reson Med 71:1896-1905, 2014. © 2013 Wiley Periodicals, In
EVALuna2:25706